Heterotopic ossification in a 7‐year‐old female patient treated with individualized homeopathy: A case report - Dionysios Tsintzas; Atul Jaggi; Latika Jaggi; Seema Mahesh; George Vithoulkas (Clinical Case Reports, 2019)
Abstract Classical homeopathy can be included among the treatment options for congenital heterotopic ossification.